Outsider or frontrunner? : recent developments under international and European law on the status of the European Union in international organizations and treaty bodies - Hoffmeister, Frank (2007)
Reviews important factual developments as regards the EU's legal status in multilateral fora, focusing roughly on the last ten years. Analyzes the related issues of internal and European law, with particular attention being paid to the European Parliament's role when the Community becomes a member of an international organization or a multilateral convention establishing treaty bodies.